PENERAPAN SISTEM KREDIT SEMESTER MERDEKA BELAJAR DI SMA NEGERI 1 GRESIK - Jaenuri, Jaenuri; Mulyani, Sri (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2024)
The purpose of writing this thesis is to determine the implementation of the Semester Credit System (SKS) at SMAN 1 Gresik. Curriculum changes from timeto time SMA Negeri 1 Gresik has become a reference school for other schools. Since the launch of Mover Schools by implementing the Kurikulum Merdeka (KUMER), it has become a challenge for school principals. As a school driving community pressure, it is inevitable to implement SKS. This is driven by the desire of the student's parents to graduate within 2 academic years. This research uses data collection techniques, triangulation method, data sources (triangulation data), researchers (triangulation investigator), as well as perspectives and theories). The results of the research showed that there were no technical guidelines for SKS in Mover Schools, so the school formed a school development team, carried out curriculum inovation and conveyed aspirations during the PMO (Project Management Office) assisting Mover Schools. SMAN 1 Gresik was the first to implement the SKS program with an independent curriculum.